Pembentukan Karakter Anak Usia Dini Melalui Metode Pembiasaan Berbasis Nilai Islam - Hirlan; Mukminah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Islamic education, rooted in the Qur'an and Sunnah, prioritizes the formation of character and morals according to its teachings. This research, therefore, investigates how student character develops from an Islamic educational perspective. To achieve this, a descriptive qualitative methodology was employed, focusing on observing and describing real-world events and phenomena. Specifically, the study details the use of the habituation method in Islamic early childhood education SDN Mertak Umbak. Findings reveal that this habituation method effectively instills Islamic educational values, evidenced by children applying learned habits, such as prayer and good conduct, in their home and social environments.